1977
DOI: 10.1042/cs0520499
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 25-Hydroxy Vitamin D3 in the Osteomalacia of Chronic Renal Failure

Abstract: 1. Five patients with the osteomalacia of chronic renal failure were given 50--100 nmol of 25-hydroxy vitamin D3 intravenously per day for 24--28 days. 2. In all five patients, during administration of 25-hydroxy vitamin D3 there was a substantial rise in the plasma concentration of 25-hydroxy vitamin D from initially abnormally low values. 3. Significant improvement in bone mineralization, intestinal calcium absorption and muscle strength occurred in the three patients with the greatest rise in plasma 25-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…These effects may be mediated by de novo protein synthesis, affecting muscle cell growth [26]. Because this effect on muscle tissues seems to result in clinical improvement even after a short-term intervention [27,28,29,30], it was of major clinical interest if vitamin D may be effective for the prevention of falls and thus fractures in elderly people. Indeed, a study showed that in vitamin D-deficient subjects, severely impaired muscle function may be present even before biochemical signs of bone disease develops [31].…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be mediated by de novo protein synthesis, affecting muscle cell growth [26]. Because this effect on muscle tissues seems to result in clinical improvement even after a short-term intervention [27,28,29,30], it was of major clinical interest if vitamin D may be effective for the prevention of falls and thus fractures in elderly people. Indeed, a study showed that in vitamin D-deficient subjects, severely impaired muscle function may be present even before biochemical signs of bone disease develops [31].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no correlation was observed between bone mineral volume and either serum levels of 1,25D, calcium or PTH, demonstrating that the major determinant of bone volume is the level of serum 25D, and suggesting that even a mild depletion of serum 25D can lead to osteopenia without significant changes to other factors. Although it is unclear whether serum 25D can directly influence the bone to maintain a healthy level of bone mineral, the observation that 25D administration, rather than calcium, improves bone mineralisation in patients with chronic renal failure, independent of changes to serum calcium and phosphate levels, supports the view that vitamin D directly promotes bone mineralisation and/or reduces bone resorption (Eastwood et al, 1974(Eastwood et al, , 1977.…”
Section: Evidence For the Role Of Vitamin D In Maintaining Skeletal Hmentioning
confidence: 83%
“…If bone cell CYP27B1 expression is not influenced by PTH, unlike the renal CYP27B1, as we have observed in previous animal studies , then local production of 1,25D may be more substrate (25D)-dependent than circulating 1,25D and would be impaired sooner by a fall in serum 25D levels below normal. This mechanism may also account for the improvement in bone mineralisation brought about by 25D administration in patients with chronic renal failure (Eastwood et al, 1977). Much more work is required, however, to understand the role of locally produced 1,25D in the bone and its role in bone cell metabolism.…”
Section: Conclusion and Questionsmentioning
confidence: 98%
“…There is little information available regarding other consequences of vitamin D deficiency or the impact of optimizing vitamin D status in this patient population [36, 37, 38]. The K/DOQI guidelines [10]recommend vitamin D supplementation in patients with hyperparathyroidism in CKD stages 3 and 4.…”
Section: Discussionmentioning
confidence: 99%